Analisis Kesalahan Siswa dalam Menyelasaikan Soal Persamaan Lingkaran Ditinjau dari Jenis Kelamin - Sinta, Selviana; Pathuddin, Pathuddin; Lefrida, Rita; Alfisyahra, Alfisyahra (Jurnal Pendidikan Matematika : Judika Education, 2024)
This study aims to describe the errors made by students in solving problems on the material of circle equations based on Newman's Error Analysis (NEA) reviewing gender differences. This type of research is Descriptive research with a qualitative approach conducted in class XI MIA 2 Madrasah Aliyah Alkhairaat Kalangkangan. This study uses a test and interview method. The subjects of the study were 36 students of class XI MIA 2 who were given a classification test to obtain data on high-ability students. Choosing 2 informants as test and interview subjects, namely one female student with the most errors and one male student with the most errors. The results of this study are (1) reading error; 2) understanding the problem (comprehension error); 3) transformation error (transformation error); 4) process skills error; 5) error in writing the final answer (encoding error). Conclusion, the teacher's ability to identify errors made by students is very important to support the improvement of the learning process. The errors found include errors in reading questions, understanding problems, and mathematical process errors that include transformation errors, process skills, and writing final answers. Teachers need to pay more attention to the early stages of understanding questions and ensure that students can master the skill process correctly in order to reduce errors in calculations and writing final answers. Keywords: Student Errors, Newman's Error Analysis (NEA), Gender